Restoring Voluntary Bimanual Activities of Patients With Chronic Hemiparesis Through a Foot-Controlled Hand/Forearm Exoskeleton - Wenyuan Chen; Guangyong Li; Ning Li; Wenxue Wang; Peng Yu; Ruiqian Wang; Xiujuan Xue; Xingang Zhao; Lianqing Liu (IEEE Transactions on Neural Systems and Rehabilitation Engineering, 2023)
A significant number of stroke patients are permanently left with a hemiparetic upper limb after the poststroke six-month golden recovery period, resulting in a drastic decline in their quality of life. This study develops a novel foot-controlled hand/forearm exoskeleton that enables patients with hemiparetic hands and forearms to restore their voluntary activities of daily living. Patients can accomplish dexterous hand/arm manipulation on their own with the assistance of a foot-controlled hand/forearm exoskeleton by utilizing foot movements on the unaffected side as command signals. The proposed foot-controlled exoskeleton was first tested on a stroke patient with a chronic hemiparetic upper limb. The testing results showed that the forearm exoskeleton can assist the patient in achieving approximately 107° of voluntary forearm rotation with a static control error less than 1.7°, whereas the hand exoskeleton can assist the patient in realizing at least six different voluntary hand gestures with a success rate of 100%. Further experiments involving more patients demonstrated that the foot-controlled hand/forearm exoskeleton can help patients in restoring some of the voluntary activities of daily living with their paretic upper limb, such as picking up food to eat and opening water bottles to drink, and etc. This research implies that the foot-controlled hand/forearm exoskeleton is a viable way to restore the upper limb activities of stroke patients with chronic hemiparesis.